2022
DOI: 10.1186/s12893-022-01518-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of laparoscopic versus open liver resection for hepatocellular carcinoma in older patients: a propensity score matching analysis

Abstract: Background The incidence of hepatocellular carcinoma (HCC) requiring surgical treatment in older patients has been continuously increasing. This study aimed to examine the safety and feasibility of performing laparoscopic liver resection (LLR) versus open liver resection (OLR) for HCC in older patients at a Japanese institution. Methods Between January 2010 and June 2021, 133 and 145 older patients (aged ≥ 70 years) who were diagnosed with HCC unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The number of patients in each study ranged from a minimum of 51 to 438. Among the 12 included studies, four were performed in China ( 22 , 23 , 29 , 30 ), three in Japan ( 20 , 27 , 28 ), two in Korea ( 25 , 31 ), one in Singapore ( 26 ), one in France ( 21 ), and one study in Italy, France, and Spain ( 24 ), respectively. Different studies define “elder patients” individually.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients in each study ranged from a minimum of 51 to 438. Among the 12 included studies, four were performed in China ( 22 , 23 , 29 , 30 ), three in Japan ( 20 , 27 , 28 ), two in Korea ( 25 , 31 ), one in Singapore ( 26 ), one in France ( 21 ), and one study in Italy, France, and Spain ( 24 ), respectively. Different studies define “elder patients” individually.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies define “elder patients” individually. Three studies ( 21 , 30 , 31 ) had an inclusion criterion of ≥65 years, eight studies ( 20 , 22 27 , 29 ) comprised patients aged ≥70 years, and one study ( 28 ) included patients who were 75 years old and above. The LLR and the OLR groups were comparable in terms of age, gender, characteristics of the tumor, and the American Society of Anesthesiologists score.…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic hepatectomy (LH) is considered safe and effective treatment for liver cancer. Studies have shown that LH has almost the same effect as traditional open surgery on HCC patients in terms of OS and RFS ( 44 , 45 ); moreover, it is associated with a lower complication rate, less intraoperative blood loss, and shorter hospital stay ( 46 , 47 ). Several recent studies comparing laparoscopic hepatectomy with percutaneous radiofrequency ablation have shown that LH is superior to percutaneous radiofrequency ablation for very-early- or early-stage HCC ( 28 , 30 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic liver resection is an alternative approach to open surgery for hepatocellular carcinoma and metastatic liver disease [55]. Liver tolerance in large animal models to intraoperative electrons has a favorable profile and is an additional area of research and development for the electron-FLASH technology [56][57][58][59].…”
Section: The Potential Of Intraoperative Electron-flash and Laparosco...mentioning
confidence: 99%